The role of CD24 as a potential biomarker for malignant pleural mesothelioma - Mohamed Shaaban Mousa; Ahmed Mamdooh Ghoname; Dalia Abd El-Kareem Ateya; Hamed A H Abdallah; Salwa Hassan Ahmed (Egyptian Journal of Chest Disease and Tuberculosis, 2023)
Objectives Pleural mesothelioma is a rapidly progressing pleural neoplasm caused by asbestos exposure of a long latency around 30-40 years. Patients with mesothelioma are usually diagnosed at a late stage with poor outcomes in terms of morbidity and mortality with 6–12 months’ median survival. Despite the prohibited use of asbestos, malignant pleural mesothelioma is still increasingly being occurred in young age and female patients. Different un-standardized biomarkers have been used to diagnose MPM as mesothelin and febulin with controversial results, so we used CD 24 as a biomarker to diagnose and differentiate between different subtypes of malignant pleural mesothelioma. Materials and methods Our cohort study included total of fifty-nine patients with exudative pleural effusion. All patients underwent full history taking, clinical examination, blood tests (CBC, coagulation profile, liver and kidney functions), tapping of pleural effusion and to send pleural fluid investigations for LDH, albumin, total protein and albumin, then confirmed exudative pleural effusion patients were subjected to thoracic ultrasonography and medical thoracoscopy for the majority of cases or ultrasound guided biopsy in selected cases to obtain pleural biopsies for histopathology and then the examination of pleural biopsies for CD24 expression. Results Our study demonstrated the possibility of using CD24 as a biomarker in the immunostaining of pleural biopsies to differentiate between malignant pleural mesothelioma and pleural malignancy other than mesothelioma (18 mesothelioma cases versus 2 nonmesothelioma malignant cases) with high statistical significance P value < 0.001 and also it can discriminate between subtypes of mesothelioma as it showed marked significance in epithelioid subtype (12 epithelioid versus 1 sarcomatoid versus 5 biphasic subtypes) with more uptake by score +2 in epithelioid mesothelioma. Conclusions CD24 can be supposed to be a routine biomarker for immunohistochemistry of pleural tissue samples in diagnosis of mesothelioma and it can be used to differentiate between subtypes of malignant mesothelioma subtypes.